Riding Fences: Anticipatory Governance, Curriculum Policy, and Teacher Subjectivity - Morris, Jill; Couture, Jean-Claude; Phelan, Anne M. (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2023)
In this article we question the discursive deployment of narrowing conceptions of the future in education in three provincial cases: Alberta, British Columbia, and Ontario. Asserting that educational policy in Canada is grounded in the “future-logics” of educational innovation—reflective of an anticipatory orientation to governance—we critique concepts from each province’s curriculum policy documents: “competence,” “personalized learning,” and “professional teacher.” We ask to what extent anticipatory governance is at work in Canadian policies, and if it is, to what degree does an anticipatory strategy occlude or disrupt the objectification of curriculum and the over-determination of teacher subjectivities?